Fatores determinantes e barreiras das ecoinovações: um estudo de caso em um hotel de Fortaleza-CE - Lameu, Eva Valéria Maia (2022)
Eco-innovations consist of improvements or changes in products, services, processes or organizational methods that reduce environmental impacts. Thus, its adoption is configured as a relevant alternative for organizations, which in addition to environmental benefits, can obtain economic and social benefits. Some factors interfere, determining or hindering its creation, development or adoption. In this sense, this work has the general objective of investigating the determining factors and barriers of eco-innovations in the hotel segment. This is a qualitative research, whose strategy adopted was a single case study. The unit of analysis is a large hotel in the city of Fortaleza-CE, linked to the Brazilian Association of the Hotel Industry of Ceará (ABIHCE), having as research subjects, managers and supervisors of the hotel. Five semi-structured interviews and non-participant observation were carried out. Data analysis was carried out through content analysis, with the aid of ATLAS.ti software. The results show that the hotel adopts ecoinnovations of products, processes and organizations, whose predominant typology is the Ecoinnovation of products. It was found that market-driven factors are the main determinants of ecoinnovations, with the cost reduction factor being the most relevant. It was also found that the main barriers of eco-innovations are the barriers linked to the consumer and the financial barriers. In addition, this study revealed three empirical categories, one determining factor (Management leadership) and two types of barriers (Barriers linked to the government and Barriers linked to the owner/investor), showing that managerial leadership motivates/determines; while governments and investors make it difficult to create, develop and adopt eco-innovations in a company of the hotel segment.